Quantifying Everyday Ecologies: Principles for Manual Annotation of Many Hours of Infants' Lives - Mendoza, Jennifer K.; Fausey, Caitlin M. (Frontiers in Psychology, 2021)
Everyday experiences are the experiences available to shape developmental change. Remarkable advances in devices used to record infants’ and toddlers’ everyday experiences, as well as in repositories to aggregate and share such recordings across teams of theorists, have yielded a potential gold mine of insights to spur next-generation theories of experience-dependent change. Making full use of these advances, however, currently requires manual annotation. Manually annotating many hours of everyday life is a dedicated pursuit requiring significant time and resources, and in many domains is an endeavor currently lacking foundational facts to guide potentially consequential implementation decisions. These realities make manual annotation a frequent ‘off ramp’ en route to discoveries, as theorists instead opt for narrower scoped activities. Here, we provide theorists with a framework for manually annotating many hours of everyday life designed to reduce both theoretical and practical overwhelm. We share insights based on our team’s recent adventures in the previously uncharted territory of everyday music. We identify principles, and share implementation examples and tools, to help theorists achieve scalable solutions to challenges that are especially fierce when annotating extended timescales. These principles for quantifying everyday ecologies will help theorists collectively maximize return on investment in databases of everyday recordings and will enable a broad community of scholars – across institutions, skillsets, experiences, and working environments – to make discoveries about the experiences upon which development may depend.